Reaction dynamics studies for the system 7Be+58Ni. (March 2015) - Torresi, D; Mazzocco, M.; Acosta, L; Boiano, A; Boiano, C; Diaz-Torres, A; Fierro, N; Glodariu, T; Grilj, L; Guglielmetti, A; Keeley, N; La Commara, M; et al.
Abstract: The study of reactions induced by exotic weakly bound nuclei at energies around the Coulomb barrier had attracted a large interest in the last decade, since the features of these nuclei can deeply affect the reaction dynamics. The discrimination between different reaction mechanisms is, in general, a rather difficult task. It can be achieved by using detector arrays covering high solid angle and with high granularity that allow to measure the reaction products and, possibly, coincidences between them, as, for example, recently done for stable weakly bound nuclei [1, 2]. We investigated the collision of the weakly bound nucleus 7 Be on a 58 Ni target at the beam energy of 1.1 times the Coulomb barrier, measuring the elastic scattering angular distribution and the energy and angular distributions of 3 He and 4 He. The 7 Be radioactive ion beam was produced by the facility EXOTIC at INFN-LNL with an energy of 22 MeV and an intensity of ~3×10 5 pps. Results showed that the 4 He yeld is about 4 times larger than 3 He yield, suggesting that reaction mechanisms other than the break-up mostly produce the He isotopes. Theoretical calculations for transfer channels and compound nucleus reactions suggest that complete fusion accounts for (41±5%) of the total reaction cross section extracted from optical model analysis of the elastic scattering data, and that 3 He and 4 He stripping are the most populated reaction channels among direct processes. Eventually estimation of incomplete fusion contributions to the 3, 4 He production cross sections was performed through semi-classical calculations with the code PLATYPUS [3].